The impact of a Metaverse-based educational program and the development of educational and technological methodology for the gymnastics lesson - Ameen Atta Hassan (Khatulistwa Education Center, 2026)
Background The importance of the study is due to the real-time interaction during the lesson and sharing with the members of the classroom together, and the presence of diverse spaces that are similar to or superior to real spaces in which virtual life is practiced. Time series coding of data for the educational process. Objectives The purpose of this paper is to how the metaverse affects the development of the technological methodology for the physical education lesson. Methods The researcher used the descriptive method within the framework of studies and theoretical literature related to the study and similar, and the experimental method by applying and analyzing the study variables, the study community was second-stage students in the College of Physical Education and Sports Sciences, and the research sample was selected from Section D and their number was (10) students, the scientific methodology of the study was to apply technological variables and augmented reality and virtual reality to the course of the physical education lesson by choosing to explain the gymnastics skill. Results The results were the sum of the average arithmetic mean for the physical education lesson with metaverse applications (2.96), the highest percentage of technological influence on the physical education lesson and data science standards at a rate of (5.6), the percentage of improvement in the use of metaverse applications at a rate of (40%) and the application of metaverse technologies in various games for physical education. Conclusion In conclusion, there is a statistically significant difference in the initial measurements of the experimental group regarding the percentage contribution of the metaverse application to the development of physical education courses.